Foetal lung volumes in pregnant women who deliver very preterm: a pilot study - Story, Lisa; Zhang, Tong; Steinweg, Johannes K.; Hutter, Jana; Matthew, Jacqueline; Dassios, Theodore; Seed, Paul T.; Pasupathy, Dharmintra; Allsop, Joanna; Hajnal, Joseph V.; Greenough, Anne; Shennan, Andrew H.; et al. (Pediatric Research, 2020)
Background: Infants born preterm are at increased risk of pulmonary morbidity. The contribution of antenatal factors to impairments in lung structure/function has not been fully elucidated. This study aimed to compare standardized lung volumes from foetuses that were delivered <32 weeks’ gestation with foetuses that were delivered >37 weeks. Methods: Fourteen women who delivered <32 weeks gestation and 56 women who delivered >37 underwent a foetal MRI. Slice-volume reconstruction was then used and the foetal lungs were then segmented using multi-atlas approaches. Body volumes were calculated by manual segmentation and lung:body volume ratios generated. Results: Mean gestation at MRI of the preterm group was 27+2 weeks (SD 2.9, range 20+6–31+3) and control group 25+3 weeks (SD 4.7 range 20+5–31+6). Mean gestation at delivery of the preterm group was 29+2 weeks (SD 2.6, range 22+0–32+0). Lung:body volume ratios and foetal lung volumes were smaller in foetuses that were delivered preterm both with and without preterm premature rupture of membranes compared to those born at term (p < 0.001 in all cases). Conclusions: Foetuses that were delivered very preterm had reduced lung volumes when standardized for foetal size, irrespective of ruptured membranes. These are novel findings and suggest an antenatal aetiology of insult and possible focus for future preventative therapies.
CRIS-Team Scopus Importer:2023-03-08